Sources of value in takeovers: Synergy or restructuring–implications for target and bidder firms - Chatterjee, Sayan (Strategic Management Journal, 1992)
Abstract Advocates of the market for corporate control argue that takeover bids should be accepted because unsuccessful targets tend to lose market value. Other researchers argue that takeover bids should be rejected because the combined firms often perform poorly. However, missing in this debate is the influence of the source of takeover gains on the decision to reject or accept takeover bids. This study posits that value from takeovers can be created by synergy or restructuring. The study suggests that only if the synergy component is dominant should the target firm agree to be taken over. The study then tests the dominance of the source of value in takeovers by examining takeovers that were unsuccessful. The study concludes that, first, restructuring, not synergy, motivated the sample studied and target firms can create the same value independently. Second the need for restructuring was industry‐wide. However, even if restructuring is the motive behind a takeover, the target firm has to carry out the restructuring, failing which it does not create any value. The study also suggests reasons for the ambiguous findings in the strategic management merger literature.